PERFORMANCE COMPARISON OF ISLAMIC BANKS AND CONVENTIONAL BANKS IN PAKISTAN - Rizwan, Rabeea (International Journal of Islamic Banking and Finance Research, 2021)
The objective of this paper is to compare and analyze the performance of Islamic Banks and Conventional Banks operating in Pakistan during the 5 year period of 2015-2019. This study utilizes the CAMEL approach to assess and compare the performance of Islamic Banks and Conventional Banks in Pakistan using a sample of banks. For the purpose of this study, we have used a sample of 4 Conventional banks and 4 Islamic Banks that are operating in Pakistan. All the relevant information for the purpose of comparison for this study was collected from the annual reports of these sample banks which were available on the respective bank’s website. The findings of this study indicate that in Pakistan, Islamic banks have performed better in terms of asset quality and earnings than the conventional banks whereas the conventional banks had a better performance in terms of liquidity, management efficiency and capital during the five-year period of consideration. The findings of the analysis also showed that Islamic banks in Pakistan have shown significant growth over the 5 year period 2015-2019.